2018
DOI: 10.2196/10292
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Designed Mobile-Based Computerized Cognitive Addiction Therapy App for the Improvement of Cognition Impairments and Risk Decision Making in Methamphetamine Use Disorder: Randomized Controlled Trial

Abstract: BackgroundCognitive rehabilitation therapy has been found to improve cognitive deficits and impulse control problems in methamphetamine use disorder (MUD). However, there is limited research regarding this therapy’s feasibility when using mobile-based health technologies in supporting recovery from MUD in China.ObjectiveThe main aim of this study was to test whether 4 weeks of a newly designed computerized cognitive addiction therapy (CCAT) app can improve cognitive impairments, eliminate drug-related attentio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 45 publications
0
61
0
1
Order By: Relevance
“…Computerized cognitive addiction therapy (CCAT) represents another computer/digital‐based therapy with potential therapeutic benefit for treating methamphetamine addiction (Zhu et al, ). Previous findings demonstrate cognitive function and decision making as predictors of long‐term prognosis in methamphetamine use.…”
Section: Treatment Of Mapmentioning
confidence: 99%
See 3 more Smart Citations
“…Computerized cognitive addiction therapy (CCAT) represents another computer/digital‐based therapy with potential therapeutic benefit for treating methamphetamine addiction (Zhu et al, ). Previous findings demonstrate cognitive function and decision making as predictors of long‐term prognosis in methamphetamine use.…”
Section: Treatment Of Mapmentioning
confidence: 99%
“…CCAT methods have been shown to produce cognitive benefits for both schizophrenia and substance use disorders. A pilot RCT of a novel mobile‐based CCAT app for methamphetamine use found that CCAT therapy improved performance on both cognitive function (Chinese version of CogState Battery) and impulse control tasks (e.g., Balloon Analog Risk Task, Delay Discounting Task, Iowa Gambling Task) when compared with treatment as usual controls (d'Amato et al, ; Zhu et al, ).…”
Section: Treatment Of Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…Kapitány-Fövény et al [52] presented an interactive application that focuses on the prevention of psychoactive substance use by developing six modules: (1) interactive comics/cartoons, telling recovery stories; (2) quiz game; (3) role play; (4) introduction of psychoactive drugs; (5) information on the somatic and psychological effects of psychoactive substances; (6) list of available treatment units, rehabilitation and self-help groups in Hungary. Zhu et al [53] concluded that computerized cognitive therapy helps cognitive impairment and impulse control of patients with substance use disorder and invited them to continue with this research line for the understanding of the underlying brain mechanisms of cognitive therapy. Finally, Kiluk et al [54], through a review of the literature, found results that show benefits in interventions based on Cognitive Behavioral Therapy developed through technology with chronic alcohol consumers.…”
Section: Neuropsychological Rehabilitation For Addictionsmentioning
confidence: 99%